2020
DOI: 10.1029/2019jd032273
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Interferometry Uncertainty, Beam Steering Interferometry, and Evidence of Lightning Being Ignited by a Cosmic Ray Shower

Abstract: We present an uncertainty analysis on correlation-based time delay estimate, the basis for broadband lightning interferometry. A normal interferometry would yield much higher uncertainties than the theoretically predicted lower bound due to finite correlation window lengths. However, if the signals are aligned in time, the uncertainties approach the lower bound and can be used to indicate the interferometric uncertainties. Based on this, we introduce a beam steering interferometry technique. It first estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 36 publications
(98 reference statements)
1
36
0
Order By: Relevance
“…We thus interpret this fast shift as an artifact of the change from negative dominant to positive dominant VHF emissions. During the transition, the VHF processing identifies weighted source locations between the true source locations of the upward and downward streamers (Shao et al, 2020 These MFB events are strong evidences, which prove that simultaneous and continuous downward positive and upward negative streamer development occurs in FB. Even when the streamers of one polarity dominate the overall VHF emissions, the streamers of the other polarity continue to propagate.…”
Section: Further Insight From Mixed Fast Breakdownmentioning
confidence: 78%
See 1 more Smart Citation
“…We thus interpret this fast shift as an artifact of the change from negative dominant to positive dominant VHF emissions. During the transition, the VHF processing identifies weighted source locations between the true source locations of the upward and downward streamers (Shao et al, 2020 These MFB events are strong evidences, which prove that simultaneous and continuous downward positive and upward negative streamer development occurs in FB. Even when the streamers of one polarity dominate the overall VHF emissions, the streamers of the other polarity continue to propagate.…”
Section: Further Insight From Mixed Fast Breakdownmentioning
confidence: 78%
“…Understanding how lightning initiates in air remains a challenging one due to the difficulty of direct observations in a thunderstorm (Marshall et al., 2005; Rakov & Uman, 2003; Smith et al., 1999; Willett et al., 1989). Radio imaging of lightning with broadband interferometry is a widely adopted technique that can effectively detect detailed development of the lightning breakdown and has been improved persistently by many studies (Lyu et al., 2019; Rhodes et al., 1994; Rison et al., 2016; Shao et al., 1995, 2018, 2020; Stock et al., 2014, 2017; Sun et al., 2013; Tilles et al., 2019). Rison et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is useful to remember that it is assumed that SCRs might play an important role in lightning initiation by providing seed energetic electrons and the ionization necessary for breakdown processes (e.g., Dwyer and Uman, 2014). Recently, Shao et al (2020) performed a detailed radio frequency interferometry of the fast positive breakdown process that started a normal intracloud lightning and concluded that the breakdown process was ignited by a cosmic ray shower. Thus, there is a possibility that the discovered ∼27-day modulation of SCRs that is primarily caused by the ∼27-day periodicity in the HMF and solar wind, which influences the primary CRs entering the Earth's atmosphere, could also modulate lightning occurrence.…”
Section: Phase Relations and Lightning Activitymentioning
confidence: 99%
“…Very-high-frequency (VHF) and VLF/low-frequency (LF) systems are distinguished based on the different frequency ranges of operation, pulse rates, and amplitudes in the RF spectrum [4]. In the VHF band, lightning mapping systems are commonly carried out using the interferometry (ITF) and time of arrival (TOA) technique or time difference of arrival technique (TDOA) [15][16][17][18][19][20][21][22][23]. Compared with the TOA and TDOA locating system, the ITF system can locate both isolated pulses and continuous emissions with a higher time resolution [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…VHF emissions can be modeled as point sources considering that VHF signals are pulses of short duration and line-of-sight propagation. Thus, the azimuth-elevation 2D direction of lightning channels can be obtained using the ITF system [18,19,23]. The 3D structure of lightning channels can be obtained using two separated broadband interferometers or by combining other detection methods such as HSV and acoustic arrays [9,24].…”
Section: Introductionmentioning
confidence: 99%